Confronting particle emission scenarios with strangeness data - Grassi, Frédérique; Socolowski Jr., Otavio [UNESP] (American Physical Society (APS), 1998)
We show that a hadron gas model with continuous particle emission instead of freeze-out may solve some of the problems (high values of the freeze-out density and specific net charge) that one encounters in the latter case when studying strange particle ratios such as those from the experiment WA85. This underlines the necessity to understand better particle emission in hydrodynamics to be able to analyze data. It also reopens the possibility of a quark-hadron transition occurring with phase equilibrium instead of explosively.